Development of a criteriabased approach to agroecological assessment of slope agrolandscapes - Alekseev, Victor; Maksimov, Vladimir; Chuchkalov, Sergey; Medvedev, Vladimir; Mishin, Petr; Kazakov, Yurij; Kondratieva, Nadezhda; Lekomtsev, Petr; Yunusov, Gubeydulla; Obolensky, Nikolaj (Eastern-European Journal of Enterprise Technologies, 2018)
For the forecast and management of erosion processes in order to protect the environment, information is needed on the state of its components and impact factors as well as the results of this impact. The existing methods for assessing the catchment area are mainly descriptive and cannot be used in mathematical prediction problems. The most accurate formulation of the problem of quantitative assessment of the catchment area is carried out during hydrological calculations. It seems expedient to develop theoretical prerequisites for agroecological assessment of slope agrolandscapes on the stability of a network of temporary watercourses by using the Lokhtin criterion. Slope agrolandscapes are erosive dangerous objects. The existence of a continuously changing system of microstreams generated by precipitation on slopes greatly complicates the situation. Criteria are proposed to determine the main trends in the development of watercourses of river systems by washing away or depositing soil. Conclusions about the catchment area as a whole can be obtained by examining a certain area of a microstream flow for a long time and comparing field observations with laboratory experiments. To determine the sustainability of a watercourse, a theoretically reasonable value has been proposed, which allows quantifying the network of temporary streams. When conducting research, data on the catchment area of the Tsivil river (Chuvash Republic, Russia) from 1950 to 2010 were used. A quantitative assessment of the erosion resistance of the microstream system was carried out both for periods of snowmelt and for rains, conventionally divided into summer and autumn. The theoretical background considered is confirmed by the data of longterm observations on the Great Tsivil river for sixty years. The dependences obtained make it possible to compile an adequate forecast of the direction of evolution of the catchment area in relation to the processes of soil deposition or its washing out. The criteria developed are applicable both to a specific catchment area of microstreams and to the catchment area of a river system as a whole